Pharyngo-jugular fistula after "salvage" total laryngectomy: a case report. (December 2015) - Crosetti, Erika; Fulcheri, Andrea; Succo, Giovanni
Abstract Introduction We present a rare case of pharyngo-jugular fistula in a patient who underwent salvage total laryngectomy after organ-sparing radiochemotherapy. Case presentation A 77-year-old Caucasian man underwent total laryngectomy and bilateral neck dissection as salvage surgery after the failure of radiochemotherapy at another hospital. Thirty-five days after surgery, he was admitted to our emergency room for fever and massive oral bleeding during meals. Videopanendoscopy showed the presence of a large clot at the base of his tongue, while a neck computed tomography scan showed a pharyngo-jugular fistula with the presence of air in the left internal jugular vein. Cervicotomy was performed: the internal jugular vein was ligated and sectioned, and the pharyngeal defect was repaired with a pectoralis major myocutaneous flap. The postoperative period was uneventful. Twenty-five days post surgery, videofluorography showed the fistula had disappeared. Our patient then began oral feeding without complications and was discharged. At present, 5 years after the operation, our patient is alive and shows no evidence of disease. Conclusions Pharyngo-jugular fistula is an uncommon complication after total laryngectomy, especially in the chemoradiation era, which is potentially fatal if not promptly treated.